Fiscal Transfers and Fiscal Sustainability - Niklas Potrafke; Markus Reischmann (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine whether US and German state governments pursue sustainable fiscal policies taking into account fiscal transfers. Using panel data techniques we investigate whether the debt-to-GDP ratio had a positive influence on the primary surplus (Bohn-model). We show that including/excluding fiscal transfers changes the results. If fiscal transfers are not included in the primary surplus, the test results do not indicate that the US and German state governments pursued sustainable fiscal policies. Our results also suggest that fiscal transfers were positively related with debt. These findings indicate that intergovernmental transfers have implicitly subsidized debts.
Keywords: H72; H74; H77; C23; 330; fiscal sustainability; public debt; institutions; fiscal transfers; panel data